The Effect of Competence, Infrastructure and Accessibility on Patients’ Satisfaction at the Puskesmas in Kabupaten Indragiri Hulu (International Journal of Scientific Research and Management (IJSRM), 2019)
This study aimed to analyze the effect of competency, infrastructure and accessibility on patients’ satisfaction at Puskesmas (health centers) in Kabupaten Indragiri Hulu. The population in this study was daily visitors at three Puskesmas with unknown numbers. The number of samples was calculated by using Yamani formula and 97 respondents were taken as the samples. They were the patients who got treatment at the Puskesmas in Kabupaten Indragiri Hulu. These sample were chosen through proportional random sampling method. The data of this study were collected by distributing a closed questionnaire. Then, the data were measured by using Likert scale. After that, the data were analyzed by employing SEM (Structural Equation Modeling) analysis which was operated through Smart PLS 3 Application. The results of this study indicated that: (1) Competence had a positive and significant effect on patients’ satisfaction; (2) Infrastructure had a positive and significant effect on patients’ satisfaction (3) Accessibility had a positive and significant effect on patients’ satisfaction.